NEW RECORD OF COCHLIOBOS HAWAIIENSIS ALCORN ASSOCIATED WITH BUTTON SHEDDING AND PREMATURE NUTFALL IN COCONUT IN INDIA - A. Karthikeyan; R. BIL4SKARAN (International Coconut Community, 1996)
From the shed buttons and immature nuts of coconut, a jungus was isolated which on artificial inoculation in coconut bunches of varying ages caused button shedding and premature nutfall. The fungus was identified as Cochliobolus hawaiiensis Alcorn. Buttons up to 4 months age were susceptible to the fungus. Among the thirteen coconut genotypes studied, infection was high in Lakshadweep Micro, Lakshadweep Ordinary an d East Coast Tall x Malaysian Green Dwarf (ECT x MGD). Carboxin 75 WP (500 ppm and above), mancozeb and copper oxy chloride (1000 ppm and above) completely inhibited the mycelial growth of C hawaiiensis under in vitro conditions. In Vivo, mancozeb (0.2%) was very effective for the control of the disease.